2015
DOI: 10.1038/mto.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

ATN-224 enhances antitumor efficacy of oncolytic herpes virus against both local and metastatic head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most frequent cancer worldwide, and the 5-year survival rates are among the worst of the major cancers. Oncolytic herpes simplex viruses (oHSV) have the potential to make a significant impact in the targeted treatment of these patients. Here, we tested antitumor efficacy of RAMBO, an oHSV armed with the antiangiogenic Vstat120, alone and in conjunction with ATN-224, a copper chelator against HNSCC in vitro and in vivo animal models. We found that all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Evaluation of changes in tumor microenvironment after oHSV therapy have uncovered changes in vascularization post therapy inciting several studies combining virotherapy with vascular disrupting agents and angiogenesis inhibitors (37). We have previously demonstrated increased anti-tumor effects when arming oHSV with Vstat120, a 120 kDa cleaved secreted fragment of BAI1, against a variety of preclinical cancer models, including glioblastoma, ovarian cancer, and head and neck cancer (6, 32, 38, 39). These effects had been heretofore attributed to the antiangiogenic effect of Vstat120 mediated by its conserved type I thrombospondin type I repeats (TSR), which bind to CD36 on endothelial cells and induce Fas-mediated apoptosis (12, 13).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of changes in tumor microenvironment after oHSV therapy have uncovered changes in vascularization post therapy inciting several studies combining virotherapy with vascular disrupting agents and angiogenesis inhibitors (37). We have previously demonstrated increased anti-tumor effects when arming oHSV with Vstat120, a 120 kDa cleaved secreted fragment of BAI1, against a variety of preclinical cancer models, including glioblastoma, ovarian cancer, and head and neck cancer (6, 32, 38, 39). These effects had been heretofore attributed to the antiangiogenic effect of Vstat120 mediated by its conserved type I thrombospondin type I repeats (TSR), which bind to CD36 on endothelial cells and induce Fas-mediated apoptosis (12, 13).…”
Section: Discussionmentioning
confidence: 99%
“…Female athymic nu/nu (Target Validation Shared Resource, The Ohio State University) or C57BL/6 male mice (Jackson Laboratories), aged 4–5-weeks, were injected subcutaneously with SCC-74A (1.5 × 10 7 ) or MTE (murine syngeneic) (1 × 10 6 ) cells in a volume of 100 μL into the rear flank, respectively. Mice were then recruited into studies and randomized into treatment groups as previously described 33 . For SCC-74A (human xenograft) studies, mice were treated with 2 × 10 9 PFU Reolysin on days 0 and 7 post-recruitment and SAHA (50 mg/kg) was administered via intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…injection on days 1, 3, 5, 8, 10, and 12. Tissues were harvested at the indicated time points for ex vivo killing 38 or immune cell phenotypic assessment and for tumor H&E immunohistochemistry (when tumors reached ∼1,500 mm 3 ) 33 as described. Animals were observed daily and tumor volumes were obtained as previously described 33 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid Antiangiogenesis Mediated By Oncolytic Virus (RAMBO) is a Vasculostatin-expressing oHSV [14]. In our previously studies, we showed that the RAMBO virus significantly enhance antitumor and anti-angiogenic efficacy in preclinical models of GBM, head and neck squamous cell carcinoma (SCC), and ovarian cancers through its ability to reduce angiogenesis [14][15][16]. Due to the prominent anti-angiogenic activity of RAMBO, we hypothesized that it would be also effective against highly vascularized malignant STSs.…”
Section: Introductionmentioning
confidence: 99%